Analisis Islamicity Performance Index serta Pengaruhnya terhadap Kinerja Keuangan pada Perbankan Syariah Periode 2017-2022 - Rahmawati, Yunika; Djatnika, Djoni; Setiawan; Nurdin, Ade Ali (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
As an institution that upholds the values of social responsibility and aspects of spirituality apart from just the aspect of financial performance, sharia banking requires a measurement ratio that is able to assess conformity of principles with sharia rules as well as a tool that can express accountability. So this research has a purpose to analyze the approach of the Islamicity Performance Index ratio and see its effect on Islamic Commercial Banking Financial Performance as a proxy for ROA. Measurements were made using the PSR, ZPR, EDR, and IivsNII ratios as a measure of social and economic performance aspects. The samples that fit with the criteria are seven Islamic Commercial Banks for the 2017–2022 period. This research use the descriptive-quantitative method with the random Effect Model (REM) which the chosen data analysis model. The result is that these ratios simultaneously affect ROA. While partially only the ratios of PSR, ZPR, and EDR have an effect.